2013
DOI: 10.2224/sbp.2013.41.5.861
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Military Identity: Scale Development and Psychometric Evaluations

Abstract: Our purpose was to perform a psychometric evaluation of a new 33-item questionnaire developed in Norway. To evaluate it we assessed its internal consistency, performed an exploratory factor analysis, and investigated aspects of construct validity. We also examined test-retest reliability. A second purpose was to investigate whether or not individual level variables such as age, gender, or service were related to different military identities. In Study 1 we collected cross-sectional data from military personnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 39 publications
1
36
2
2
Order By: Relevance
“…Furthermore, he also questions the benefit of cadets being educated in an institute more or less isolated from the rest of the organisation. In previous attempts to introduce a general military operational identity, shortfalls have been associated with undervaluing institutional features such as serving a greater cause and also overstating the significance of aspects related to warfighting (Johansen, Laberg & Martinussen, 2013).…”
Section: Officer Identitymentioning
confidence: 99%
“…Furthermore, he also questions the benefit of cadets being educated in an institute more or less isolated from the rest of the organisation. In previous attempts to introduce a general military operational identity, shortfalls have been associated with undervaluing institutional features such as serving a greater cause and also overstating the significance of aspects related to warfighting (Johansen, Laberg & Martinussen, 2013).…”
Section: Officer Identitymentioning
confidence: 99%
“…Since the end of the Cold War, the military role has been qualified as a unidimensional bipolar construct (Franke 1999a(Franke , 1999bReed and Segal 2010). The more a soldier takes on the role of a warrior, the less the soldier takes on the role of a peacekeeper, and vice versa.1 Although Johanson et al (2013) conceptualized military identity as a multidimensional construct, besides idealism, professionalism and individualism, they used "warriorism" as a typical military component, but did not focus on the peacekeeper role. With the construction of the Warrior Peacekeeper Role Identity Questionnaire (WPRIS), it was demonstrated that the concept of military role identity is a bidimensional construct: Dutch soldiers identify with both roles simultaneously, and a preference for one role is not related with a preference for the other role (Broesder 2011;; Op den Buijs and Broesder 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Being deployed to such operations probably represents a hallmark of their soldiering, and one could assume that such an experience further strengthens their personal skills, tactical skills and overall military identity. The military operational identity encompasses professionalism and warriorism (Johansen, Laberg and Martinussen, 2013a;2013b). Even though operational identity is regarded as valuable for a military organisation, it might also give cause for concern.…”
mentioning
confidence: 99%
“…This might imply that soldiers become less motivated for peacetime service aimed at territorial defence. Additionally, a professionalisation of the Armed Forces might recruit self-centred individuals and thus promote individualistic values (Eriksson, 2004(Eriksson, , 2007Johansen et al, 2013a). To better understand important motivational characteristics of the soldiers, the current study examines whether a deployment to international operations strengthens or weakens military identities.…”
mentioning
confidence: 99%